2017
DOI: 10.1080/10942912.2017.1297952
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and bioactivities of polysaccharide from spentHovenia dulcispeduncles by alkali pretreatment

Abstract: A novel heteropolysaccharide named SHDP was isolated from spent Hovenia dulcis peduncles (SHD) using alkali extraction. The preliminary characterization of the polysaccharide was performed by physicochemical and spectral methods. The bioactivities in vitro were also investigated. The results indicated that SHDPs are homogeneous with an average molecular weight of approximately 4570 kDa, and contain uronic acid (2.3%) and protein (3.6%). It is mainly composed of rhamnose, fucose, arabinose, xylose, mannose, glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It can promote digestion, produce saliva, quench thirst, antifebrile, and relieve hangovers [6]. Previous results indicated that both polyphenolics and polysaccharides obtained from H. dulcis exhibit a variety of bioactivities, such as antioxidant activities [4,[7][8][9][10], hypoglycemic activities [10,11], and immunostimulatory activity [12]. In addition, natural polyphenolic-protein-polysaccharide complexes (PPPs) extracted from the peduncle of H. dulcis have also been proved to exhibit strong in vitro antioxidant activity, anti-glycation activity, and anti-hyperglycemic effects [6].…”
Section: Introductionmentioning
confidence: 99%
“…It can promote digestion, produce saliva, quench thirst, antifebrile, and relieve hangovers [6]. Previous results indicated that both polyphenolics and polysaccharides obtained from H. dulcis exhibit a variety of bioactivities, such as antioxidant activities [4,[7][8][9][10], hypoglycemic activities [10,11], and immunostimulatory activity [12]. In addition, natural polyphenolic-protein-polysaccharide complexes (PPPs) extracted from the peduncle of H. dulcis have also been proved to exhibit strong in vitro antioxidant activity, anti-glycation activity, and anti-hyperglycemic effects [6].…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the authors highlight the many potential applications in functional products for the industry. On polysaccharides, Liu et al [ 89 ] employ alkaline extraction by stating that this extraction method is preferable for efficiency to the others, including ultrasonic extraction. This technique allowed the authors to isolate a different heteropolysaccharide denominated spent H. dulcis peduncles (SHDP).…”
Section: Nutritional Propertiesmentioning
confidence: 99%
“…However, to date, not one product is available in the European market. The high number of bioactive components contained in hydrophilic extracts, such as flavonoids, polyphenols and polysaccharides, suggested a promising application of H. dulcis , not only in the pharmaceutical sector but also in the functional food field [ 89 ]. In Europe, new food ingredient materials can be authorized only after the evaluation of their safety, according to the novel food regulation.…”
Section: Regulatory Framework For the Use Of H Dulcis mentioning
confidence: 99%